Activity Behaviors and Physiological Characteristics of Women With Advanced-Stage Ovarian Cancer: A Preliminary Cross-sectional Investigation. Issue 3 (March 2018) - Schofield, Christelle; Newton, Robert U.; Cohen, Paul A.; Galvão, Daniel A.; McVeigh, Joanne A.; Hart, Nicolas H.; Mohan, Ganendra R.; Tan, Jason; Salfinger, Stuart G.; Straker, Leon M.; Peddle-McIntyre, Carolyn J.
Abstract : Objectives: Ovarian cancer (OC) survivors experience many disease and treatment adverse effects. However, the impact of OC and its treatment on objective activity behaviors and physiological status have not been examined. The purpose of this study was to compare objectively measured activity behaviors and physiological characteristics of advanced-stage OC survivors to age-matched controls. Methods: Twenty stage III–IV OC survivors and 20 controls completed assessments of activity behaviors (7-day accelerometry), physical function (400-meter walk as indicator of cardiorespiratory fitness, repeated chair rise, 6-meter walking tests), muscle strength (1-repetition maximum and handgrip), body composition (dual-energy x-ray absorptiometry), and musculoskeletal morphology (peripheral quantitative computed tomography). Results: Compared with controls, OC survivors spent more time/day in prolonged sedentary bouts ( P = 0.039, r = 0.32), had lower cardiorespiratory fitness ( P = 0.041, r = 0.33) and upper body strength ( P = 0.023, r = 0.37), had higher areal bone mineral content ( P = 0.047, r = 0.33) and volumetric trabecular density ( P = 0.048, r = 0.31), but were not different in other measures of body composition nor in muscle morphology ( P > 0.050). Only 20% (n = 4) of OC survivors accrued 150 minutes/week or greater moderate and vigorous physical activity (MVPA) time in 10-minute bouts or greater. Moderate and vigorous physical activity time/day in 10-minute bouts or greater was strongly associated with cardiorespiratory fitness ( P = 0.001, ρ = −0.702) and lower extremity function ( P = 0.019, ρ = −0.519) and moderately associated with muscle cross-sectional area ( P = 0.035, ρ = 0.473). Conclusions: Posttreatment OC survivors spent more time in prolonged sedentary bouts and had lower cardiorespiratory fitness and upper body strength compared with controls. Moderate and vigorous physical activity was associated with physical function and muscle cross-sectional area. Future studies should test the efficacy of exercise interventions to increase MVPA, reduce sedentary behavior, and increase cardiorespiratory fitness and muscle strength in OC survivors.